ANALISIS BEDA DUA RATA-RATA METODE TIME-DRIVEN ACTIVITY-BASED COSTING PADA INDUSTRI GARMEN - Dewi, Frensisca Citra; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
The purpose of this research is to compare the difference of net profit before and after applying Time-Driven Activity-Based Costing. Sample of this research is 30 garment industries which located in Badung Regency, Bali and the method used  to collect the data are observation, interview, and documentation. The population is 176 garment industries and using purposive sampling method. The analysis method in this research is Paired Sample t-test. The result of this research that there is significant difference between net profit before and after applying Time-Driven Activity-Based Costing. Net profit of garment industry increased significantly after applying Time-Driven Activity-Based Costing.
Keywords: Time-Driven Activity-Based Costing; net profit; garment industry